The Effect of Transdermal Application of Ananas comosus Peel Extract on Lowering Blood Pressure: A Randomized Controlled Trial - Palupi, Eva Riantika Ratna; Sandi, Yudisa Diaz Lutfi; Rahmawati, Rahmi (Babali Nursing Research, 2026)
Aims: This study examined whether transdermal application of Ananas comosus peel extract could effectively reduce blood pressure in elderly hypertensive patients within a primary health care setting. Methods: A randomized controlled trial was conducted at Primary Health Centre involving 86 elderly with hypertension. After exclusion and dropout, 64 participants completed the study (32 in intervention group, 32 in control group). The intervention group received daily transdermal application of Ananas comosus peel extract, while the control group received no active treatment, over seven consecutive days. Blood pressure was measured each morning and evening. Between-group differences were tested with independent t-tests; within-group changes with paired t-tests. Results: Baseline demographic and clinical characteristics did not differ significantly between groups (p > 0.05). No significant differences in systolic blood pressure (SBP), diastolic blood pressure (DBP), or mean arterial pressure (MAP) were observed between groups during Days 1–3. By Day 4, the intervention group showed significantly greater reductions in SBP (p= 0.005), DBP (p= 0.034), and MAP (p= 0.014), with progressively larger differences through Day 7 (all p< 0.001). Within the intervention group, SBP, DBP, and MAP decreased significantly from baseline to Day 7 (p< 0.001), whereas the control group exhibited minimal, non-significant changes. Conclusion: Transdermal application of Ananas comosus peel extract produced a statistically significant and time-dependent reduction in blood pressure starting from Day 4, with continued improvement until one week. These findings support its potential as a non-pharmacological adjunct in managing essential hypertension among older adults